Catorce vocales del andaluz oriental: producción y percepción de /i/, /e/, /a/, /o/ y /u/en posición final y ante /-s/, /-r/ y /-θ/ subyacentes en Almería - Herrero de Haro, Alfredo (El Colegio de México, 2019)
The present article investigates the effects of deleting /-s/, /-r/,and /-θ/ on preceding vowels. For this, the speech of 60 speakers from EasternAndalusia is analysed acoustically and an experiment is also carried outto analyse perception. From these studies we conclude that 1) deleting /-s/,/-r/, and /-θ/ changes the quality of a preceding vowel to different degrees,allowing us to identify 14 different vowels in this geolect; 2) Eastern AndalusianSpanish speakers can identify, without any contextual help, whether ornot a vowel is followed by an underlying consonant and these speakers canalso distinguish between nine different vowels.